ANALISIS EVALUASI EKONOMI SUMBER DAYA ALAM DAN LINGKUNGAN DI KABUPATEN KONAWE SELATAN - Adam, La Ode Bahana; Hasniah, Hasniah; Gandri, La; Arman, Arman (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
The condition of natural resources of forests and agricultural land, especially in South Konawe Regency, is currently quite a concern. South Konawe Regency has a forest area with a total area of 475,953 hectares, consisting of natural reserve forests, protected forests, production forests, limited production forests, other use areas, water bodies, community plantation forests, urban forests, mangrove forests and conservation forests. Among the total current forest area, there are 31,874 hectares of critical land and 6,606 hectares of very critical land. The aim of the research is to inventory the potential and management problems as well as the economic value of natural forest and agricultural land resources in South Konawe Regency. The research approach uses 5 (five) approach models, namely the political approach, the technocratic approach, the integrated top-down policy bottom-up planning approach, the participatory approach, and the regional finance approach. The type of research used in this research is qualitative research with a case study method. Research data needs were collected using questionnaires and field surveys. The data analysis methods used include Natural Resource Potential Analysis, Identification of natural resources in forests and agricultural land, as well as total economic analysis or total economic value (TEV) obtained from the sum of values based on use and values based on indirect use. The research results show that the potential forest resources of South Konawe Regency with samples from Wolasi, Laeya, and Tinanggea subdistricts are divided into 4 forest area function classes, namely protected forests, permanent production forests, limited production forests, and national parks. Protected forests covering an area of 11,273.58 ha, limited production forests covering an area of 2,860.99 ha, permanent production forests covering an area of 14,931.17 ha, and national parks covering an area of 9,246.96 ha. Meanwhile, the agricultural potential of South Konawe Regency from the research sample consists of mixed dry land farming covering an area of 14,787.73 ha, dry land farming covering an area of 1,684.39 ha, rice fields covering an area of 17,014.23 ha, and plantations covering an area of 553.44 ha. The economic value of South Konawe district's forest resources is IDR 64,152,630,168.15 per year, while the economic value of agricultural land resources is IDR 9,342,541,716/year.